The hiding place - Munier, Paula (Munier, Paula. Mercy and Elvis mysteries, 2021)
"Mercy and Elvis are back in The Hiding Place, the most enthralling entry yet in USA Today bestselling Paula Munier's award-winning Mercy Carr mystery series. When the man who killed her grandfather breaks out of prison and comes after her grandmother, Mercy must unearth the long-buried scandals that threaten to tear her family apart. And she may have to do it without her beloved canine partner Elvis, if his former handler has his way.... Some people take their secrets with them to the grave. Others leave them behind on their deathbeds, riddles for the survivors to solve. When her late grandfather's dying deputy calls Mercy to his side, she and Elvis inherit the cold case that haunted him-and may have killed him. But finding Beth Kilgore 20 years after she disappeared is more than a lost cause. It's a Pandora's box releasing a rain of evil on the very people Mercy and Elvis hold most dear. The timing couldn't be worse when the man who murdered her grandfather escapes from prison and a fellow Army vet turns up claiming that Elvis is his dog, not hers. With her grandmother Patience gone missing, and Elvis's future uncertain, Mercy faces the prospect of losing her most treasured allies, the only ones she believes truly love and understand her. She needs help, and that means forgiving Vermont Game Warden Troy Warner long enough to enlist his aid. With time running out for Patience, Mercy and Elvis must team up with Troy and his search-and-rescue dog Susie Bear to unravel the secrets of the past and save her grandmother-before it's too late. Once again, Paula Munier crafts a terrific mystery thriller filled with intrigue, action, resilient characters, the mountains of Vermont, and two amazing dogs"--